Asosiasi Siklus Hidup Perusahaan dengan Incremental Value- Relevance Informasi Laba dan Arus Kas - Sari Atmini (The Indonesian Journal of Accounting Research, 2013)
The objectives of this study is to empirically examine the association between corporate life-cycle and the incremental value-relevance of earnings and cash flows. Value-relevance is defined as the ability to explain cross-sectional variation in market value of equity.Corporate life-cycle consists of four stages: start-up, growth, mature, and decline. Firms in different life-cycle stages have different characteristics. The differences in the life-cycle stages affect the usefulness of accounting performance measures, such as earnings and cash flows.Four criteria are used to identify a start-up firm-year observation: (1) firm was founded between 1988 and 1997, (2) firm was not formed as a result of divestiture, merger, or other form of restructuring, (3) firm had no more than one year of sales history prior to going public, and (4) only the first three years  of firm s data are included after the founding date. Four classification variables are used to classify firm-year observations in to growth, mature, and decline: percent sales growth, capital expenditure as a percentage of total value of the firm, annual dividend as a percentage of income, and age of the firm. Based on these criteria, 54 firm-year observations from 41 different firm are taken as samples, consisting of 37 firm-year observation from 26 different firm in the growth stage and 17 firm-year observation from 15 different firms in the mature stage.Data are analyzed using multiple regression analysis. Because of the limitation of the samples, this study is not succeeded to test the hypothesis that relate to start-up and decline stages. The results show that market value of equity of growth firms is influenced by earnings and cash flows from financing activities. Earnings and financing cash flows associate positively with market value of equity. There are no association between cash flows from operation activities and cash flows from investments activities. Investment cash flows associate negatively with market value of equity. There are no association between earnings, cash flows from operation activities, and cash flows from financing activities and market value of equity.Overall, this study provides evidence  that corporate life-cycle influences the incremental value-relevance of earnings and cash flows. Earnings and cash flows from financing activities appear to be value-relevant in mature stage.